2021
DOI: 10.1155/2021/5536442
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam Anesthesia for MitraClip Implantation in a Patient with Advanced Heart Failure

Abstract: Remimazolam, a novel and ultrashort-acting benzodiazepine, has been available for general anesthesia in Japan. The administration of remimazolam does not induce injection pain, has been reported to have less cardiovascular depressant effects during general anesthesia, and flumazenil can antagonize the effects of remimazolam. However, in clinical trials, no patient who is complicated with severe heart failure or undergoes cardiac surgery was included. We present anesthetic management with remimazolam for MitraC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…In the first case, the patient's blood pressure was maintained after anesthesia induction, similar to previous case reports [3]. However, in case 2, the patient's blood pressure markedly decreased after anesthesia induction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the first case, the patient's blood pressure was maintained after anesthesia induction, similar to previous case reports [3]. However, in case 2, the patient's blood pressure markedly decreased after anesthesia induction.…”
Section: Discussionsupporting
confidence: 85%
“…Remimazolam is an ultrashort-acting benzodiazepine that causes hemodynamic changes [1,2]. Successful anesthesia with remimazolam has been reported in several patients with impaired cardiac function [3,4]. In the two cases we are reporting, remimazolam was utilized for the induction and maintenance of anesthesia in patients with mitral regurgitation (MR) and reduced ejection fraction during transcatheter edge-to-edge repair of the mitral valve with the MitraClip system.…”
Section: Introductionmentioning
confidence: 99%
“…Successful use of remimazolam has been described in spine surgery incorporating motor evoked potential monitoring (Kondo et al, 2020), thyroid surgery with neuromonitoring (Hayamizu et al, 2021), and cardiac surgery with cardiopulmonary bypass (Saito et al, 2021). Remimazolam's successful use in high-risk patients, including endoscopic retrograde cholangiopancreatography in a patient with impaired respiratory function due to myotonic dystrophy (Fukuda et al, 2021), MitraClip implantation in a patient with advanced heart failure (Satoh et al, 2021), and cochlear implant in a patient with mitochondrial myopathy (Suzuki et al, 2021) has been published.…”
Section: Case Reportsmentioning
confidence: 99%
“…The primary advantages of remimazolam tosilate include rapid onset of action and minimal depression of cardiorespiratory function, allowing this drug favorable in sedation and general anesthesia. Several clinical cases found that remimazolam can be used to achieve the same appropriate anesthesia management as other existing anesthetics for patients undergoing cardiac surgery [ 13 , 14 , 24 ] or for the patient undergoing non-cardiac surgery with cardiac dysfunction [ 25 ]. And two RCTs [ 12 , 15 ] suggested that remimazolam was safe and effective compared with propofol for induction in cardiac surgery with less hemodynamic fluctuations.…”
Section: Discussionmentioning
confidence: 99%